Effect of three mating types and two feeding types on reproductive parameters in guinea pig reared in the Peruvian highlands - Velásquez C., Silvia (2017)
This study aimed to evaluate the effect of three mating types and two feeding types on reproductive parameters. A total of 210 females and 30 males guinea pigs were used in a complete block design with a factorial arrangement of three mating types (post-partum, post weaning, 7-day after weaning) x two feeding types (green forage, green forage with supplement). The study included the evaluation of the reproductive performance of females between the second and third parturition. The results showed the significant effect of the mating type on birth weight, number of parturitions per year and the efficient use of estrus (p<0.05). Additionally, there was a significant effect of feeding type on birth weight (p<0.05). The interaction feeding and mating type was significant indicating that supplementation tends to improve fertility rate, litter size and annual productivity index when applying the post-partum mating; likewise, it tends to proportionally reduce them according to the interval between parturition and the beginning of mating in the postweaning and 7-day after weaning mating types (p<0.05). In guinea pig breeding in the Peruvian highlands is recommended the post-partum mating with energy supplementation instead of only green forage or post-weaning mating using green forage.